Hubungan Sosial Budaya, Pengetahuan, Sumber Informasi dengan Pemberian Mp-Asi Dini Pada Bayi Usia 0-6 Bulan - Nensi Junianti; Parida Hanum; Anastasia Wulandari; Lisa Qurniawan; Mola Suzarni; Bismawati Bismawati (Malahayati Nursing Journal, 2025)
ABSTRACT Good complementary feeding must meet the requirements, namely the right time. Giving complementary foods too early can cause digestive disorders in infants because physiologically the baby's intestines are not ready for solid food, so it can result in diarrhea or constipation. The purpose of this study was to determine the relationship between socio-culture, knowledge, and information sources with early complementary feeding in infants aged 0-6 months. The type of research used was quantitative using an analytic observational design research design with a cross sectional approach. The population in this study were all mothers who had babies 0-6 months as many as 68 people. The technique of taking subjects using total sampling as many as 68 people. The instrument used in this study was a questionnaire to assess social culture, knowledge, information sources and early complementary feeding. Data analysis was univariate and bivariate analysis with chi square test. The results explained that there was a relationship between social culture (p=0.020), knowledge (p=0.001) and information sources (p=0.001) with early complementary feeding. The conclusion of this study is that there is a relationship between social culture, knowledge and information sources with early complementary feeding in infants 0-6 months. Keywords:Socio-Culture, Knowledge, Information Source, Early Complementary Feeding, Infants ABSTRAK Pemberian MP-ASI yang baik harus memenuhi syarat yaitu waktu yang tepat. Pemberian MP-ASI terlalu dini dapat menyebabkan gangguan pencernaan pada bayi karen secara fisiologis usus bayi belum siap untuk makanan padat, sehingga dapat mengakibatkan diare atau konstipasi. Tujuan penelitian ini adalah untuk mengetahui hubungan sosial budaya, pengetahuan, sumber informasi dengan pemberian MP-ASI dini pada bayi usia 0-6 bulan. Jenis penelitian yang digunakan adalah kuantitatif dengan menggunakan desain penelitian desain observasional analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah semua ibu yang memiliki bayi 0-6 bulan sebanyak 68 orang. Teknik pengambilan subjek menggunakan total sampling sebanyak 68 orang. Instrumen yang digunakan dalam penelitian ini adalah kuesioner untuk menilai social budaya, pengetahuan, sumber informasi dan pemberian MP-ASI dini. Analisa data penelitian adalah analisis univariat dan bivariat dengan uji chi square. Hasil penelitian menjelaskan bahwa terdapat hubungan social budaya (p=0,020), pengetahuan (p=0,001) dan sumber informasi (p=0,001) dengan Pemberian MP-ASI dini. Kesimpulan penelitian ini adalah terdapat hubungan social budaya, pengetahuan dan sumber informasi dengan Pemberian MP-ASI dini pada bayi 0-6 bulan.  Kata Kunci: Sosial Budaya, Pengetahuan, Sumber Informasi, MP-ASI Dini, Bayi.